Analysis on Mobile Samsat’s Public Service Quality - Kasim, Azhar; Fathurahman, Heri (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2012)
Quality improvement in public service has become a major concern in government institutions in their effort to provide the public with maximum service. It is also a major concern for Samsat (One-Roof System) institutions in Jakarta, Bogor, Tangerang, Bekasi (Jabodetabek). The purpose of this study is to analyze the quality level of the service provided by Mobile Samsat units in Jabodetabek. The study uses the quantitative approach in order to illustrate the gap between consumer expectation of public service and consumer perception of the actual service, based on five dimensions: reliability, responsiveness, assurance, empathy, and tangibility. Measurement results of the five dimensions show that customers find the service provided by Mobile Samsat in Jabodetabek to be unsatisfactory.